HGV-Netz - Auswirkungen auf Luftverkehr und Airports. - Schudlich, Malte (DVV Media Group, 2009)
Der Ausbau des Hochgeschwindigkeitsnetzwerks hat in den vergangenen Jahren zu einer teilweise deutlichen Verschiebung im westeuropäischen Passagierverkehr geführt. Betrachtet man die Höhe der geplanten Investitionen, sind weitere Veränderungen zu erwarten. Eine genauere Betrachtung dieser Entwicklungen sollte Aufschluss über mögliche Szenarien und Handlungsoptionen geben.

The ongoing extension of Europe's high speed rail network brings about drastic journey time reductions on ever longer routes. The impact of this new travel option is of growing concern to the air transport industry. Whereas airlines tend to reduce seating capacity more often or suspend service on selected routes, airports move closer towards each other in the wake of shorter journey times resulting from railway infrastructure .improvements. The railways' impact on airlines and airports - coupled with a general diversification of the seat reservations process - leaves potential customers facing the growing complexity of travel options. Several Western European rail links have been selected to highlight how serious the Impact of high speed rail travel can be. By also taking into account the proposed volume of medium term investment in long haul rail travel, Europe's passenger air transport has to face up to profound changes, forcing airlines and airports to come to terms with this development. A high degree of flexibility is called for, together with a reappraisal of existing airline alliance models.
Europe's high speed trains and their impact on air traffic and airports.
Keywords: Verkehr; Eisenbahn; Hochleistungsschnellbahn; Luftverkehr; Erreichbarkeit; Reisezeit; Szenario; Verkehrsplanung; Verkehrsentwicklung; Flughafen; Fahrzeit; Verkehrsanteil; Verkehrsverlagerung